2004
DOI: 10.1109/tdmr.2004.829073
|View full text |Cite
|
Sign up to set email alerts
|

Gold Dendrite Simulation: Root Cause Determination

Abstract: While dendritic growth for Ag, Sn, and other metals provides jeopardy for the exterior of packaged integrated circuits, we observed Au dendrites inside ceramic packages. The key factors controlling growth kinetics are a combination of bias and two residual chemicals: one hygroscopic component from the die attach material, and gold plating salts. We found dendritic growth rate to be linear with plating salt concentration during laboratory simulations, but were unable to measure the current density dependence. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Nieman [11] has found that, during biased highly accelerated stress test (HAST), Cu migration is proportional to chloride concentration in adhesive tape and is inversely proportional to conductor spacing. Recently, Kersey and Blish [12] reported Au dendritic growth in ceramic package due to the combined factors of bias and residual components from die-attach adhesive and gold-plate salts. However, most of the works mentioned tend to focus on failure mechanisms under the given stress condition rather than the dependence of Cu migration on subassembly package materials, which is a subject of significant practical interest and needs careful attention.…”
Section: Introductionmentioning
confidence: 99%
“…Nieman [11] has found that, during biased highly accelerated stress test (HAST), Cu migration is proportional to chloride concentration in adhesive tape and is inversely proportional to conductor spacing. Recently, Kersey and Blish [12] reported Au dendritic growth in ceramic package due to the combined factors of bias and residual components from die-attach adhesive and gold-plate salts. However, most of the works mentioned tend to focus on failure mechanisms under the given stress condition rather than the dependence of Cu migration on subassembly package materials, which is a subject of significant practical interest and needs careful attention.…”
Section: Introductionmentioning
confidence: 99%